Workplace bullying: Issues, future legislative trends and solutiions. - Michael, Rene (Cambridge Publishing, 2003)
There is increasing recognition that workplace bullying occurs across the world and across occupations; an internet search will reveal several thousand sites purporting to deal with the issue, although much of the material is personal and anecdotal. Several reports have graphically illustrated the pain, mental distress, physical illness and career damage suffered by victims of bullying. Of concern is the evidence that is accumulating on bullying and its effects amongst health professionals, particularly in the nursing profession. This paper discusses workplace bullying, issues, legislative nds and possible solutions to assist in dealing with this growing concern.